Validation of an Innovative Chromatographic Method for Hypericin Quantification in Nanostructured Lipid Carriers - de Araújo, Patricia Rocha [UNESP]; Sato, Mariana Rillo [UNESP]; Luiz, Marcela Tavares [UNESP]; Chorilli, Marlus [UNESP] (Oxford University Press (OUP), 2023)
Background: Hypericin (HYP) is a natural compound widely used as a food supplement. The encapsulation of HYP into nanosystems, such as nanostructured lipid carriers (NLC), is a promising strategy for delivering this lipophilic molecule and protecting it from degradation. Objective: This study aims to develop and validate an analytical method to quantify the encapsulation efficiency of HYP in NLC. Method: A reverse-phase high-performance liquid chromatography (HPLC) method was developed and validated according to the International Conference on Harmonization (ICH) guide Q2 (R1). NLC was prepared through the ultrasonication method, and HYP encapsulation efficiency was evaluated using the validated method. Results: Separation was achieved using an isocratic mobile phase composed of acetonitrile, methanol, and ammonium acetate buffer (10 mM, pH 5.0) (54:36:10, v/v/v) and a reverse stationary phase. The specificity, linearity, precision, accuracy, and robustness of the method were assessed and confirmed during the validation. Furthermore, the validated method was able to determine the encapsulation efficiency of HYP in NLC. Conclusions: The HPLC method was validated, and the results indicated the ability of NLC to deliver HYP compounds for further application as a food supplement. Highlights: HYP is used as a food supplement and for photodynamic therapy (PDT). The developed method was specific, linear, precise, accurate, and robust. NLCs showed a high ability to encapsulate HYP.